Gender-Based Risk Perception Bias and Loan Availing Decisions among Women Customers: A CFA and SEM Approach in Banking Services - B. Loganathan, B. Loganathan; P. Sasikumar, P. Sasikumar (Journal of Neonatal Surgery, 2025)
This study examines the influence of gender-related biases on women's decisions to access formal loan services in the banking sector. Using a structured questionnaire and analysing responses through Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) with AMOS, this research evaluates six principal constructs: perceived financial risk, procedural complexity, institutional trust, social influence, gender stereotype bias, and loan planning decision. The results demonstrate that trust in institutional systems significantly enhances women's financial engagement, whereas procedural and perceptual barriers adversely affect the likelihood of women seeking credit. These findings contribute to the expanding discourse on gender-inclusive financial systems and offer data-driven insights for policymaking and banking reforms.